ISTIKHDAM ATH-THARIQAH AL-MUBASYARAH FII TA’LIM MAHARAH AL-ISTIMA’ - Ridha, Muhammad; Riyadi, Slamet (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
Listening skill instruction is often neglected by Arabic language teachers, as evidenced by their incorrect selection of listening teaching methods. Theoretically, choosing the direct method for listening instruction is the right decision. Therefore, the researcher chose to implement the direct method for listening instruction at MTS Albarokah. This study employs classroom action research. The research data includes observations obtained directly during the implementation of the lessons, interview data gathered from interviews between the researcher and students, and student test data before and after the lessons. The researcher aims to examine listening instruction using the direct method and assess student learning outcomes through tests administered before and after the lessons. The results of the study indicate that the implementation of the direct method must be carried out through the stages of planning, implementation, evaluation, and reflection. Moreover, student learning outcomes improved significantly after applying the direct method to listening instruction.